Cross-hybridization between HPV genotypes in the Linear Array Genotyping Test confirmed by Next-Generation Sequencing - Cristina Artaza-Irigaray; María Guadalupe Flores-Miramontes; Dominik Olszewski; Verónica Vallejo-Ruiz; Laura Patricia Limón-Toledo; Cibeles Sánchez-Roque; Rocío Mayoral-Torres; Luis Felipe Jave-Suárez; Adriana Aguilar-Lemarroy (BMC, 2019)
Abstract Background Linear Array Genotyping Test (LA) is one of the gold standards used for Human Papillomavirus (HPV) genotyping, however, since its launching in 2006, new HPV genotypes are still being characterized with the use of high specificity techniques such as Next-Generation Sequencing (NGS). Derived from a previous study of the IMSS Research Network on HPV, which suggested that there might be cross-reaction of some HPV genotypes in the LA test, the aim of this study was to elucidate this point. Methods Double stranded L1 fragments (gBlocks) from different HPVs were used to perform LA test, additionally, 14 HPV83+ and 26 HPV84+ cervical samples determined with LA, were individually genotyped by NGS. Results From the LA HPV83+ samples, 64.3% were truly HPV83+, while 42.9% were found to be HPV102+. On the other hand, 69.2% of the LA HPV84+ samples were HPV84+, while 3.8, 11.5 and 30.8% of the samples were indeed HPV 86, 87 and 114 positive, respectively. Additionally, novel nucleotide changes in L1 gene from HPV genotypes 83, 84, 87, 102 and 114 were determined in Mexican cervical samples, some of them lead to changes in the protein sequence. Conclusions We demonstrated that there is cross-hybridization between alpha3-HPV genotypes 86, 87 and 114 with HPV84 probe in LA strips and between HPV102 with HPV83 probe; this may be causing over or under estimation in the prevalence of these genotypes. In the upcoming years, a switch to more specific and sensitive genotyping methods that detect a broader spectrum of HPV genotypes needs to be implemented.